Braxon®-assisted prepectoral breast reconstruction: A decade later - Bassetto, Franco; Pandis, Laura; Facchin, Federico; Azzena, Gian Paolo; Vindigni, Vincenzo (Frontiers in Surgery, 2022)
At the edge of a bioengineered breast era, implant-based breast reconstruction is broadening, and biotechnology research is increasingly empowering clinical practice. As never before, the choice of biomaterials has become a key moment for reconstructive outcomes, and the rise of acellular dermal matrices (ADMs) in this surgical field is a prime example of profound upheaval and progress. With the advent of prepectoral breast reconstruction (PPBR) plenty of biomaterials have been developed to wrap the synthetic prosthesis completely or partially, however leading to enormous confusion and dissent on the feasible reconstructive strategies as well as on the original scientific rationale underlying the prepectoral technology. Braxon® is the very first ADM that made prepectoral positioning possible, wrapping-around the prosthesis and exerting the ADM's proven regenerative power on the implant-tissue interface, taking advantage of the body’s physiological healing mechanisms. To date, the Braxon® method is among the most studied and practiced worldwide, and more than 50 publications confirm the high performance of the device in the most varied clinical scenarios. A comprehensive collection of the experience of this pioneering device is still missing. With this review we want therefore to provide a concrete understanding and decision-making tool in the field of prepectoral breast surgery, through a more in-depth knowledge of the prepectoral initiator, a decade later.